2003
DOI: 10.1046/j.1095-8649.2003.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Social learning of prey location in hatchery‐reared Atlantic salmon

Abstract: Naïve, hatchery‐reared Atlantic salmon Salmo salar parr were paired with demonstrators that had been pre‐trained to accept live prey from the surface or from the benthos. After 6 days of observing demonstrators through a clear perspex partition the naïve fish's benthic foraging skills were tested. The results revealed that hatchery‐reared Atlantic salmon can be taught to target benthic prey items by observation alone and social learning protocols can be utilized to dramatically increase benthic foraging succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Either the fish remembered this food from their time of rearing, or they preferred chironomidae larvae as food in the wild, because the PFG also preferred these taxa. It is well known that during the larval phase, the fish will hunt for exactly the same or for similar items they had successfully captured in their first feeding trials (Kieffer and Colgan, ; Brown et al., ,b; Nunn et al., ). This type of learning is important to remember, as it may take minutes or hours before live food is again encountered.…”
Section: Discussionmentioning
confidence: 99%
“…Either the fish remembered this food from their time of rearing, or they preferred chironomidae larvae as food in the wild, because the PFG also preferred these taxa. It is well known that during the larval phase, the fish will hunt for exactly the same or for similar items they had successfully captured in their first feeding trials (Kieffer and Colgan, ; Brown et al., ,b; Nunn et al., ). This type of learning is important to remember, as it may take minutes or hours before live food is again encountered.…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect to releasing fish in open systems is the rate at which stocked fish emigrate, and the factors driving emigration. As released fish are reared in a relatively benign hatchery environment that experiences little variation, they lack exposure to many natural stimuli that may invoke particular responses, such as the movement of mobile prey or rapid changes to hydrographic conditions (Brown & Laland 2001Brown et al 2003). Ideally, pilot studies are used to refine release strategies, but these may not always reveal the effects of extrinsic factors on released fish and their subsequent responses (Kawabata et al 2007;Lebata et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Such interpretation is consistent with a number of previous studies. For example, it has been found that foraging by hatchery fish can be improved by exposure to live prey and through social learning from demonstrators (Brown et al , 2003 a , b ), and that juvenile S. salar reared under structurally complex environments display higher feeding rates than those reared under barren conditions (Rodewald et al , ). The idea that foraging success of stocked S. salar may be inversely related to duration of artificial rearing is consistent with the observation that S. salar parr begin feeding on natural prey sooner after release than pre‐smolts, even when they are stocked simultaneously (Larsson et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Esocids reared with artificial vegetation show reduced startle responses and preference for vegetated habitats (Einfalt et al , ). In salmonids, enrichment and predator conditioning have been shown to improve crypsis (Donnelly & Dill, ; Maynard et al , ), foraging ability (Brown et al , 2003 a , b ; Rodewald et al , ), neural plasticity (Salvanes et al , ), antipredatory behaviours (Berejikian et al , ; Brown, ; Vilhunen, ; Roberts et al , ) and use of shelters, which may reduce cortisol levels (Näslund et al , ), at least under laboratory or semi‐natural conditions. More generally, development under favourable conditions ( i.e .…”
Section: Introductionmentioning
confidence: 99%